Determination of volumetric gas–liquid mass transfer coefficient of carbon monoxide in a batch cultivation system using kinetic simulations - Robert Lovitt (Bioresource Technology, 2017)
A mathematical model of microbial kinetics was introduced to predict the overall volumetric gas–liquid mass transfer coefficient (kLa) of carbon monoxide (CO) in a batch cultivation system. The cell concentration (X), acetate concentration (Cace), headspace gas (Nco and Nco2), dissolved CO concentration in the fermentation medium (Cco), and mass transfer rate (R) were simulated using a variety of kLa values. The simulated results showed excellent agreement with the experimental data for a kLa of 13 /hr. The Cco values decreased with increase in cultivation times, whereas the maximum mass transfer rate was achieved at the mid-log phase due to vigorous microbial CO consumption rate higher than R. The model suggested in this study may be applied to a variety of microbial systems involving gaseous substrates.